Fast Implementation of Binary Field Multiplication on Arm Helium with Applications to Post-Quantum Signatures - Oliveira, Eric Azevedo de; Gazzoni Filho, Décio Luiz; Rodrigues, Felix Carvalho; López, Julio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
Polynomial multiplication over binary fields GF(2 n ) is a major bottleneck in post-quantum cryptographic algorithms, demanding constant-time implementations on constrained devices. This paper presents constant-time algorithms for multiplication and squaring in GF(2 n ), with n ∈ {128, 192, 256}, tailored for the Arm Cortex-M85 and applied to the AIMer and FAEST signature schemes. By leveraging the VMULLB and VMULLT carry-less multiplication instructions from the Helium MVE extension, we deliver vectorized routines integrated into the reference codebases of both schemes. Benchmarks on the Renesas EK-RA8M1 board show speedups of up to 1.35× for AIMer and 1.30× for FAEST-EM.